A semantic analysis of the Kankana-ey word adi - Palayen, Jemamiah M.
This is a study which focuses on the different meanings of the Kankana-ey Adi. Using J.L. Agustin's Speech Act Theory (1962) along with the Leech's Seven Types of meaning (1974), this study looks at meanings of adi and how they become performative with the meanings they produce. The study looks at the Conceptual and Associative meanings of the Kankana-ey Adi. With these meanings, the study uses the concept of Illocutionary Act in Austin's Speech Act Theory, in explaining the act being performed by the language from these meanings in using the word adi. This study also uses some concepts from Geoff Thompson's Functional Grammar (2004), in explaining how the adi behaves such that it is able to produce multiple affective meanings. Descriptive analysis is the primary approach of this study. It records daily conversations from Kankana-ey speaking community, and extracts dialogues from 3 Kankana-ey films -- Author's abstract.